Corticospinal Excitability Preceding the Grasping of Emotion-Laden Stimuli - Nogueira Campos, Anaelli Aparecida (2014)
Evolutionary theories posit that emotions prime organisms for action. This study examined whether corticospinal excitability (CSE) is modulated by the emotional valence of a to-be-grasped stimulus. CSE was estimated based on the amplitude of motor evoked potentials (MEPs) elicited using transcranial magnetic stimulation (TMS) and recorded on the first dorsal interosseous (FDI) muscle. Participants were instructed to grasp (ACTION condition) or just look at (NO-ACTION condition) unpleasant, pleasant and neutral stimuli. TMS pulses were applied randomly at 500 or 250 ms before a go signal. MEP amplitudes were normalized within condition by computing a ratio for the emotion-laden stimuli by reference to the neutral stimuli. A divergent valence effect was observed in the ACTION condition, where the CSE ratio was higher during the preparation to grasp unpleasant compared to pleasant stimuli. In addition, the CSE ratio was lower for pleasant stimuli during the ACTION condition compared to the NO-ACTION condition. Altogether, these results indicate that motor preparation is selectively modulated by the valence of the stimulus to be grasped. The lower CSE for pleasant stimuli may result from the need to refrain from executing an imminent action.